2013
DOI: 10.1103/physrevc.87.024901
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical equilibration of strongly interacting “infinite” parton matter within the parton-hadron-string dynamics transport approach

Abstract: We study the kinetic and chemical equilibration in "infinite" parton matter within the partonhadron-string dynamics off-shell transport approach, which is based on a dynamical quasiparticle model (DQPM) for partons matched to reproduce lattice QCD results-including the partonic equation of state-in thermodynamic equilibrium. The "infinite" parton matter is simulated by a system of quarks and gluons within a cubic box with periodic boundary conditions, at various energy densities, initialized out of kinetic and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(130 citation statements)
references
References 73 publications
(110 reference statements)
10
119
1
Order By: Relevance
“…As may be observed, in all these calculations the ratio ζ/s decreases monotonically with temperature. We might mention here that, such a behavior of decreasing bulk viscosity to entropy ratio was also observed in estimations based on PHSD transport codes [36] as well as in the linear sigma model in the large N limit [38]. This is in contrast with results in Refs.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…As may be observed, in all these calculations the ratio ζ/s decreases monotonically with temperature. We might mention here that, such a behavior of decreasing bulk viscosity to entropy ratio was also observed in estimations based on PHSD transport codes [36] as well as in the linear sigma model in the large N limit [38]. This is in contrast with results in Refs.…”
Section: Resultscontrasting
confidence: 56%
“…The ratio, η/s, in the hadronic phase has been estimated using UrQMD transport in Ref. [35] while the bulk and shear viscosity coefficients have been estimated using parton hadron string dynamics(PHSD) transport code within a relaxation time approximation [36]. The rise of bulk viscosity coefficient near the transition temperature has been observed in various effective models like chiral perturbation theory [37], quasiparticle models [23], linear sigma model [25] and the Nambu-Jona-Lasinio model [39].…”
Section: Introductionmentioning
confidence: 99%
“…the elliptic flow v 2 could quantitatively be well described by ideal hydrodynamics up to transverse momenta of the order of 1.5 GeV/c [9][10][11][12][13][14]. Recent studies of 'QCD matter' in equilibrium -using lattice QCD calculations [15,16] or partonic transport models in a finite box with periodic boundary conditions [17,18] -have demonstrated that the ratio of the shear viscosity to entropy density η/s should * Electronic address: Thorsten.Steinert@theo.physik.uni-giessen.de have a minimum close to the critical temperature T c , similar to atomic and molecular systems [19]. On the other hand, the ratio of the bulk viscosity to the entropy density ζ/s should have a maximum close to T c [18] or might even diverge at T c [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There are various models which can be used to study the region near T c , which we call the "semi" Quark-Gluon Plasma. This includes Parton Hadron String Dynamics [50][51][52][53][54][55], Polyakov loop models [56][57][58], the functional renormalization group [59][60][61][62][63][64][65][66][67][68][69][70], background field methods [71][72][73], and lastly, matrix models [74][75][76][77][78][79][80][81][82][83][84][85].…”
Section: Jhep10(2015)005mentioning
confidence: 99%